2022
DOI: 10.7150/ijbs.68591
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and calcium-related proteins in endometrial cancer: opportunities for pharmacological intervention

Abstract: Intracellular calcium ions are key second messengers and play an important role in malignant transformation and cancer progression. Estrogen can evoke intracellular calcium increases through membrane-initiated effects and activate subsequent kinase cascades within minutes in normal and cancerous epithelial cells. Ca 2+ -related proteins are expressed in normal epithelial cells or endometrial cancer cells, some of which are upregulated by estrogen. Both estrogen-induced transient calcium increases and long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 149 publications
(193 reference statements)
0
8
0
Order By: Relevance
“…There were also studies showing that, as an atypical cadherin, FAT2 could exert biological functions through the Hippo pathway, which is closely related to the maintenance of tissue homeostasis and to multiple processes including cancers 36,37 . In our study, patients with FAT2 mutations were identified enriched in the cAMP and calcium signaling pathway, and cAMP and calcium signaling pathways participated in cell proliferation, migration, and metastasis of UCEC 38,39 . Moreover, we investigated the expression differences of various immune cells between FAT2 mutation and wild‐type tumor tissues.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There were also studies showing that, as an atypical cadherin, FAT2 could exert biological functions through the Hippo pathway, which is closely related to the maintenance of tissue homeostasis and to multiple processes including cancers 36,37 . In our study, patients with FAT2 mutations were identified enriched in the cAMP and calcium signaling pathway, and cAMP and calcium signaling pathways participated in cell proliferation, migration, and metastasis of UCEC 38,39 . Moreover, we investigated the expression differences of various immune cells between FAT2 mutation and wild‐type tumor tissues.…”
Section: Discussionmentioning
confidence: 80%
“… 36 , 37 In our study, patients with FAT2 mutations were identified enriched in the cAMP and calcium signaling pathway, and cAMP and calcium signaling pathways participated in cell proliferation, migration, and metastasis of UCEC. 38 , 39 Moreover, we investigated the expression differences of various immune cells between FAT2 mutation and wild‐type tumor tissues. We found higher expression of activated CD4/CD8 T cells and plasmacytoid dendritic cells in FAT2 mutation patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that abnormal changes in amplitude of cytoplasmic free Ca 2+ concentration and duration of Ca 2+ elevation may promote breast cancer cell proliferation and invasion [17,21]. Te same phenomenon was confrmed in endometrial and colorectal cancers [22,23].…”
Section: Introductionmentioning
confidence: 72%
“…Cows also had greater protein expression/cell of AHR and a tendency for greater CYP1A2 mRNA, a target of AHR activation. AHR expression can be induced by IL6 signaling and AHR activation can upregulate transcription and synthesis of IL6 (Stobbe-Maicherski et al, 2013; Huang et al, 2022). Interestingly, AHR activation is involved with wasting syndrome (Girer et al, 2021) and obesity related fatty liver and inflammation (Pohjanvirta, 2017; Bock, 2021) and participates in leukocyte energy metabolism, neutrophil chemotaxis, and bacterial clearance (Partida-Sánchez et al, 2001; Bunaciu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%